2018
DOI: 10.3389/fimmu.2018.01992
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Obesity Elicits Macrophage Infiltration and Reduction in Spine Density in the Hypothalami of Male but Not Female Mice

Abstract: Increasing prevalence in obesity has become a significant public concern. C57BL/6J mice are prone to diet-induced obesity (DIO) when fed high-fat diet (HFD), and develop chronic inflammation and metabolic syndrome, making them a good model to analyze mechanisms whereby obesity elicits pathologies. DIO mice demonstrated profound sex differences in response to HFD with respect to inflammation and hypothalamic function. First, we determined that males are prone to DIO, while females are resistant. Ovariectomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(129 citation statements)
references
References 111 publications
18
111
0
Order By: Relevance
“…Obesity is considered a state of chronic inflammation as opposed to acute inflammation elicited by LPS injection [24, 25, 81]. Thus, we exposed male C57BL/6J mice to HFD or to CTR diet for 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Obesity is considered a state of chronic inflammation as opposed to acute inflammation elicited by LPS injection [24, 25, 81]. Thus, we exposed male C57BL/6J mice to HFD or to CTR diet for 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Centrally administered cytokines also provoked reduced LH and GnRH levels, but the mechanism whereby these cytokines mediate their effects is unknown [16, 17, 21-23]. More recently, our group determined that low-grade, chronic inflammation caused by high-fat diet (HFD)-induced obesity may also directly affect GnRH neurons, resulting in reduced levels of LH in circulation and diminished GnRH mRNA levels in the hypothalamus, specifically in male mice [24]. We, and others, have reported that diet-induced obese mice and people exhibited increased levels of proinflammatory cytokines, TNF-α, IL-1β, and IL-6, in circulation [24, 25] and in the hypothalamus, at the mRNA level and protein level [24, 26].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations